Self-interacting dark matter and small-scale gravitational lenses in galaxy clusters - Yang, Daneng; Yu, Hai-Bo (Physical review. D, 2021)
Recently, Meneghetti et al. reported an excess of small-scale gravitational lenses in galaxy clusters. We study its implications for self-interacting dark matter (SIDM) compared with standard cold dark matter (CDM). We design controlled N-body simulations that incorporate observational constraints. The presence of early-type galaxies in cluster substructures can deepen gravitational potential and reduce tidal mass loss. Both scenarios require a relatively high baryon concentration in the substructure to accommodate the lensing measurements, and their tangential caustics are similar. The SIDM substructure can experience gravothermal collapse and produce a steeper density profile than its CDM counterpart, leading to a larger radial galaxy-galaxy strong-lensing cross section, although this effect is hard to observe. Our results indicate that SIDM can provide a unified explanation to small-scale lenses in galaxy clusters and stellar motion in dwarf galaxies.